MICRO-NUTRIENT FORMULATIONS FOR AGRICULTURE Part-H. Copper, Zinc, Manganese and Chromium Preparation (Biological Sciences - PJSIR, 2022)
Micro-nutrient formulations for agriculture purposes have been produced mounting copper, zinc, manganese andchromium on five-different frilled compositions. Release of elements was monitored by extracting the metals with ammoniumcitrate solution and estimating them by means of an atomic absorption spectrophotometer. The results show thatrelease of copper can be controlled at a level of 1.4 to 4 ppm, that of zinc at 1.7 to 5.2 ppm, manganese at 1.8 to 8.6 ppm,while that of chromium at 0.02 to 0.3 ppm, by leachings, spread over a period of one hour to 10 days.